Biometric parameters of the Redline torpedo fish Puntius denisonii Day 1865, an endemic barb in the Western Ghats Hotspots of Southern India - Sajan Sajeevan; Anna Mercy Thoranam Varkey; Malika Vadakkedath (International Journal of Aquatic Biology, 2014)
Studies on the biometric parameters of a species to have an important role in its population or stock management and conservation. Present study investigated the morphometric, meristic, length-weight relation (LWRs), length-length relation (LLRs) and growth status (K and Kn) of the Redline torpedo barb, P. denisonii collected during August 2012 to July 2013 from river Valapattanam, Kerala. The length-weight relationship was established for monthly to differentiate growth variation and also separately calculated for males, females pooled and indeterminate. Length-length relationship, morphometric and meristic characteristics were also represented by the equation: Y = a + bX. The length-weight relations established for males was: log W = -2.207 + 3.148 log L; for females: log W = -2.360 + 3.316 log L; for indeterminate: log W = -2.176 + 3.171 log L and for pooled was: log W = -2.076 + 3.030 log L.  The regression coefficients between pooled, indeterminate, males and females of P. denisonii did not show any significant variation from isometric growth (p<0.05). All morphological characters were highly correlated with total length and correlation coefficient (r) was highest for standard length (0.9889) and pre anal length (0.9904) and lowest for pelvic fin length (0.6150). Based on the study fin formula can be written as D 2-9, P 17, V 9, A 1-6 and C 22-24.